ChemInform Abstract: Change of the Cerium Valence with Temperature — Structure and Chemical Bonding of HT‐CeRhGe. Issue 37 (22nd August 2013) - Svitlyk, Volodymyr; Hermes, Wilfried; Chevalier, Bernard; Matar, Samir F.; Gaudin, Etienne; Vosswinkel, Daniel; Chernyshov, Dmitry; Hoffmann, Rolf‐Dieter; Poettgen, Rainer
Abstract Polycrystalline CeRhGe is prepared by arc‐melting of the elements and characterized by synchrotron powder XRD and DFT calculations.